2012
DOI: 10.1186/1741-7015-10-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of iron treatment efficiency among non-anemic but iron-deficient female blood donors: a randomized controlled trial

Abstract: BackgroundIron deficiency without anemia is related to adverse symptoms that can be relieved by supplementation. Since a blood donation can induce such an iron deficiency, we investigated the clinical impact of iron treatment after a blood donation.MethodsOne week after donation, we randomly assigned 154 female donors with iron deficiency without anemia, aged below 50 years, to a four-week oral treatment of ferrous sulfate versus a placebo. The main outcome was the change in the level of fatigue before and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
64
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 39 publications
8
64
0
Order By: Relevance
“…Similar drop-out rates (38.5 %) were reported by Maghsudlu et al [12] while higher percentage (47.5 %) of dropout was reported by other study [14]. In the study by Rosvik et al [15] and Waldvogel and others [16] 28.2 ± 3.0 (24.1-43.9)…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Similar drop-out rates (38.5 %) were reported by Maghsudlu et al [12] while higher percentage (47.5 %) of dropout was reported by other study [14]. In the study by Rosvik et al [15] and Waldvogel and others [16] 28.2 ± 3.0 (24.1-43.9)…”
Section: Discussionsupporting
confidence: 75%
“…Whereas in the Placebo group mean Hb decreased significantly from 13.3 to 12.8 gm/dl. Similar decrease in Hb was observed in other studies [16,19]. This reflects increase in haematopoiesis in the iron group due to oral iron supplementation.…”
Section: Drop Outsupporting
confidence: 74%
See 1 more Smart Citation
“…The effects of iron on hemoglobin concentration seem to be similar to those observed in postpartum nonanemic women, 14 military women with iron deficiency 15 and nonanemic women following blood donation. 16 These changes apparently occur within six weeks of starting treatment. 13 Patterson and colleagues' observational findings suggested that iron could improve quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, blood markers do not necessarily reflect iron stores in other compartments. A recent study 16 suggests that following blood donation, iron supplementation can improve erythropoiesis without affecting fatigue or muscular function. Therefore, fatigue might only occur once iron deficiency becomes present in brain tissue.…”
mentioning
confidence: 99%